Online control of combine reel height in presence of farm roughness using an on-off controller - Zendehdel, Nadia (Array, 2019)
Adjusting the harvesting combine reel height in presence of the farm rough surface reduces the harvest losses, prevents possible damage to the headland and increases gravel harvest. Regarding the importance of the issue, in this study, the dynamics of the reel height control system of the John Deere1055 combine was modeled and the controllability and observability of the obtained transfer function is determined in state space. After that, with the aim of cutting the stem from a suitable point, an on-off controller is designed to keep the reel height from the ground in a permitted range. At this stage, a reduced model system is used as an approximated system to design a controller. The designed controller is simulated in MATLAB. In this simulation, the roughness of the ground was considered as the control loop noise with the normal probability distribution function. The results confirm that the reel height change is kept in the specified range against the farm roughness. The laboratory sample was also constructed using an independent excitation circuit DC motor, an optical distance sensor, and a micro controller. The experimental test shows that the height control system responses to changes in surface height at an appropriate speed without any oscillation in range.